2023
DOI: 10.9734/ijecc/2023/v13i102913
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Soil Fertility Status of Research Farm, College of Agriculture and Research Station, Katghora, Korba, Chhattisgarh

Divya Sahu,
L.K. Srivastava,
S. S. Porte
et al.

Abstract: Total 102 soil surface samples (0-15) were collected from each field of research farm, College of Agriculture, and Research Station Katghora, Korba, (C.G.) to evaluated the soil fertility status, The soil samples were analysed by standard procedures with respect to pH, EC, OC, macronutrients (N, P, K, S) and micronutrients (Fe, Mn, Cu, Zn, and B). The results showed that soil pH varied from 4.31 to 5.42 with mean 4.79 and indicated that the soils were found to be moderately acidic to strongly acidic in soil re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The available B in the sub-watershed was sufficient and ranged from 0.20 to 4.50 mg kg -1 with mean and SD value of 1.56 and 0.64, respectively [41,42] (Table 4). The CV of 40.97 per cent for available B content indicates that, it varied spatially in the sub-watershed.…”
Section: Available Micronutrientsmentioning
confidence: 99%
“…The available B in the sub-watershed was sufficient and ranged from 0.20 to 4.50 mg kg -1 with mean and SD value of 1.56 and 0.64, respectively [41,42] (Table 4). The CV of 40.97 per cent for available B content indicates that, it varied spatially in the sub-watershed.…”
Section: Available Micronutrientsmentioning
confidence: 99%
“…For example, Sahu et al (2023) conducted an assessment of SF status in three research region, Katghora, Korba, and Chhattisgarh in India. According to the NIV, the studied soils for N, P, K, B, and Sulphur (S) were classi ed in low fertility classes, phosphorus and zinc in the medium fertility class, and Fe, Mn, and Cu in the high fertility class (Sahu 2023). Kashiwar et al (2023) found that Zn, Fe, and B as soil micronutrients, were de cient in 61.9%, 59%, and 100% of the soil samples, respectively.…”
Section: Introductionmentioning
confidence: 99%